2019
DOI: 10.2147/jpr.s160504
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of physician-diagnosed neuropathic pain in Brazil

Abstract: ObjectivesEstimate the prevalence of neuropathic pain (NeP) among chronic pain patients attending Brazilian hospitals and pain clinics in São Paulo, Ceara, and Bahia and explore clinical characteristics by subtypes: painful diabetic peripheral neuropathy (pDPN), central neuropathic pain (CNP), chronic low back pain with a neuropathic component (CLBP-NeP), postherpetic neuralgia (PHN), post-traumatic neuropathic pain (PTN), and post-surgical neuropathic pain (PSN).MethodsPhysicians screened patients reporting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
2
13
0
3
Order By: Relevance
“…The BPI reported an average of seven points for pain intensity. These data corroborate an epidemiological study on the prevalence of painful diabetic neuropathy in the states of São Paulo, Ceará, and Bahia, Brazil, by applying the DN4 and BPI instruments, with scores above seven points (43). In conclusion, hyperalgesia and allodynia are related to high scores on the numerical pain scale, and this reflects in daily-life and professional activities, items assessed by the BPI (9).…”
Section: Discussionsupporting
confidence: 86%
“…The BPI reported an average of seven points for pain intensity. These data corroborate an epidemiological study on the prevalence of painful diabetic neuropathy in the states of São Paulo, Ceará, and Bahia, Brazil, by applying the DN4 and BPI instruments, with scores above seven points (43). In conclusion, hyperalgesia and allodynia are related to high scores on the numerical pain scale, and this reflects in daily-life and professional activities, items assessed by the BPI (9).…”
Section: Discussionsupporting
confidence: 86%
“…Our analysis confirms that pain is more common in women between the ages of 50 s and 60 s, while most of them live in the city. A higher frequency of neuropathic pain in the middle-age population was also observed in a work carried out in Brazil [46].…”
Section: Epidemiologysupporting
confidence: 68%
“…From the regression model, the DASH score showed statistically significant differences between the groups in that the neuropathic group demonstrated impaired upper limb function (P = 0.002). More important, the DASH score mean of 35 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) in the nonneuropathic group versus 51 (41-67) in the neuropathic group met the minimum clinical important difference in change scores, indicating that these groups are not only statistically but also clinically different. 18 Due to the heavily skewed distribution of pain scores, the 11-point NPRS was analyzed based on percentages of those experiencing pain (NPRS 1 or higher) versus no pain.…”
Section: Resultsmentioning
confidence: 98%
“…Neuropathic pain symptoms correlate with higher medical comorbidities, higher reported pain intensity, and greater disability burden than other causes of pain. 31 33 This often results in poorer prognosis, and studies have identified higher levels of depression and disability. 34 , 35 Pain catastrophizing and pain acceptance are important in treatment outcomes, and a multidisciplinary focus has been suggested for this population.…”
Section: Discussionmentioning
confidence: 99%